QoS Assurance Key Technologies in Space-Ground Heterogeneous Network - Lin LIN; Bin ZHU; Zelin WANG; Guangquan WANG; Haipeng YAO; Tao DONG; Weiying FENG (天地一体化信息网络)
The high dynamics of the topology structure, the high variability of the links between space and ground, and the highly limited network resource in the space-ground heterogeneous network pose significant challenges.To address these challenges, a space-ground heterogeneous joint QoS assurance scheme was proposed based on deep analysis of space-ground heterogeneous network development situation.The cross-domain network resource orchestration, construction of a space-ground QoS system, dynamic policy control of heterogeneous joint QoS, and on-demand adaptation and deployment of space-ground network resources technologies were discussed.